Recursive Engine In-Cylinder Pressure Estimation Using Kalman Filter and Structural Vibration Signal. Issue 31 (2018) - Han, Runzhe; Bohn, Christian; Bauer, Georg
Abstract: The cylinder pressure signal is a very useful indicator for modern high-performance internal-combustion (IC) engines. Unfortunately, direct measurements of the cylinder pressure are impractical because installing cylinder transducers is difficult and conditions in IC engine cylinders are adverse. Therefore, different methods have been investigated to reconstruct the cylinder pressure from externally measured signals, such as the engine structure vibration and the crank angular speed. In this paper, some of existing methods are reviewed firstly. Then a novel recursive cylinder pressure estimation method based on using the Kalman filter with the engine structure vibration signal as input is proposed. Two combustion metrics, pressure peak ( P max ) and peak location ( P loc ), were used for evaluating the proposed method. The estimation results were compared with the experimental data collected from a four-cylinder diesel engine and showed the effectiveness of the proposed method.